IODINE AS A POTENTIAL FRONT-LINE DEFENSE AGAINST COVID-19: A LITERATURE REVIEW - Das Bhowmik, Aneek; Das Bhowmik, Narayan; Baisya, Oindrila (Asian Journal of Pharmaceutical and Clinical Research, 2023)
The novel coronavirus disease, first identified in 2019 known as COVID-19, is caused by a new strain of severe acute respiratory syndrome coronavirus (SARS-CoV or SARS-CoV-1), named SARS-CoV-2. Recent studies showed that the virus may be airborne and spreads through small respiratory droplets of saliva in aerosols, indirect or direct physical contact with the affected individual, in a similar way to the cold and influenza. Emerging studies also demonstrate the importance of the throat along with salivary glands as sites of viral replication and transmission in early COVID-19 infection. The most common route of entry of SARS-CoV-2 is the upper respiratory tract (nasopharynx) that slowly reaches the lower respiratory tract to infect the epithelial cells within the lungs which can cause lung damage and severe respiratory symptoms, if not treated immediately. Averting colonization of the virus in the nasopharynx could be one of the best options to reduce the incidence of severe infection. It has been well-documented that iodine is one of the most effective of all antimicrobials available. Hospitals and medical facilities worldwide use povidone-iodine (PVP-I) as a standard of care in infection control. Several research studies during the ongoing COVID-19 pandemic showed the in vitro and in vivo efficacy of iodine-containing solutions such as PVP-I (Betadine), Iodine-V (Essential Iodine Drops) etc. and other iodine complexes to effectively kill the SARS-CoV-2 virus within few seconds to hours. Few commercially available iodine-containing gargling, mouthwash, and nasal spray solutions have been recommended to use in humans against SARS-CoV-2 infection by experts to prevent viral spread, especially among health workers. The present article aims to summarize these studies and highlights the rationale, safety and recommendations of use of iodine as an effective method to decrease the viral load during the early COVID-19 infection.